Optimization study on the hydrogen peroxide pretreatment and production of bioethanol from seaweed Ulva prolifera biomass. (August 2016) - Li, Yinping; Cui, Jiefen; Zhang, Gaoli; Liu, Zhengkun; Guan, Huashi; Hwang, Hueymin; Aker, Winfred G.; Wang, Peng
Highlights: Ulva prolifera residue was used as a feedstock for bioethanol production. H2 O2 pretreatment is the first to use in marine biomass to obtain fermentable sugar. Reducing sugar yield was 0.42 g/g UPR higher than earlier report. Abstract: The seaweed Ulva prolifera, distributed in inter-tidal zones worldwide, contains a large percentage of cellulosic materials. The technical feasibility of using U. prolifera residue (UPR) obtained after extraction of polysaccharides as a renewable energy resource was investigated. An environment-friendly and economical pretreatment process was conducted using hydrogen peroxide. The hydrogen peroxide pretreatment improved the efficiency of enzymatic hydrolysis. The resulting yield of reducing sugar reached a maximum of 0.42 g/g UPR under the optimal pretreatment condition (hydrogen peroxide 0.2%, 50 °C, pH 4.0, 12 h). The rate of conversion of reducing sugar in the concentrated hydrolysates to bioethanol reached 31.4% by Saccharomyces cerevisiae fermentation, which corresponds to 61.7% of the theoretical maximum yield. Compared with other reported traditional processes on Ulva biomass, the reducing sugar and bioethanol yield are substantially higher. Thus, hydrogen peroxide pretreatment is an effective enhancement of the process of bioethanol production from the seaweed U. prolifera .